(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This paper will show that the Castilian civil law contributed to the generic differentiation between men and women in the sixteenth century in the New Spain, but above all, the establishment of social roles or roles for each member of the family, which contributed to the formation of unequal power relations in favor of the paterfamilias and the subjection of the wife and children. Also, through the study of private correspondence, if what was stablished by the standard translated into practical, concrete everyday habits and behaviors.